Przepływy finansowe między gminą a bankiem - na przykładzie Poznania - Kotlińska, Janina (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The contacts between a municipality and a bank can take different forms but the result, however, is usually cash flow. Cash flow between a municipality and a bank is a direct outcome of the municipality having an account with the banks; therefore the banks render services such as: budget related services, depositing free financial means, granting loans and credits for current operations as well as future investments. The cash flow increases the volume of means to be used by local authorities, however, it also creates obligatory fees to be paid such as: account related fees, commissions on banking operations and interest on current and long-term credit. Municipalities need banks not only to deposit their temporarily free funds and take credits for current operations and future investments but also to have access to more complicated and complex services and to get assistance with cash flow management. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 273-281